Analysis of the Forms of Work as for Overcoming Deadaptation Manifestations of the Future Educators in Higher Educational Establishment - Zdanevych, Larisa (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The author reveals theoretical approaches to the problem, interprets the views of other researchers. The problem of higher educational establishment deadaptation is cleared up in the article, interpretation of the phenomenon of teenagers’ deadaptation in different spheres of psychological-pedagogical science is given. At the modern stage deadaptation is understood as a totality of features and manifestations, which affirm inconsistency of a person’s interaction with his or her environment. And as deadaptation ruins the results, which were achieved in the process of adaptation, it is necessary in the first place to found out the essence of this phenomenon. Literature analysis and practical experience of work in the pedagogical university allow us to determine some characteristics of social status of a student of the first years of study. The analysis of different forms of pedagogical work as foe the overcoming of deadaptation manifestations of the future educators in higher educational establishment is done. The author analyses the questionering conducted at the faculty of pre-school education, which allows to affirm that at the beginning of study students overcome educational difficulties and aren’t very thoughtful as for the perspectives of their future professional activity. In this period great responsibility is on the academic group supervisors. To prevent the manifestations of deadaptation the supervisors should should create psychological comfort in the group for the students – desirable for students state, affirming harmony in the inner, psychological and social life. To avoid the manifestations of deadaptation of the students-freshmen and in order to accelerate their adaptation, we have created the program for special course for the teachers and supervisors of academic groups